2005
DOI: 10.1161/circulationaha.104.495903
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of 622 Adults With Asymptomatic, Hemodynamically Significant Aortic Stenosis During Prolonged Follow-Up

Abstract: Most patients with asymptomatic, hemodynamically significant AS will develop symptoms within 5 years. Sudden death occurs in approximately 1%/y. Age, chronic renal failure, inactivity, and aortic valve velocity are independently predictive of all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
353
6
24

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 740 publications
(396 citation statements)
references
References 19 publications
13
353
6
24
Order By: Relevance
“…In this study,25 2‐year event‐free survival was 30% for patients with Vmax >4.4 m/s versus 60% for patients with Vmax <4.4 m/s. Among 622 asymptomatic patients with AS and Vmax ≥4 m/s, a Vmax ≥4.5 m/s was associated with an ≈50% increased risk of cardiac events (death or AVR)26 in a report on 116 asymptomatic patients with severe AS, a Vmax ≥5.5 m/s was associated with almost 90% increase in the risk of events (death or AVR) 27. These studies undeniably validated Vmax as an outcome marker in AS, but the cutoff for identifying patients in whom the severity of the valvular obstacle is critical remains unclear, especially for patients with no or minimal symptoms, as reflected by the different criteria used to define “very severe AS” proposed by US and European guidelines 1, 2.…”
Section: Discussionmentioning
confidence: 97%
“…In this study,25 2‐year event‐free survival was 30% for patients with Vmax >4.4 m/s versus 60% for patients with Vmax <4.4 m/s. Among 622 asymptomatic patients with AS and Vmax ≥4 m/s, a Vmax ≥4.5 m/s was associated with an ≈50% increased risk of cardiac events (death or AVR)26 in a report on 116 asymptomatic patients with severe AS, a Vmax ≥5.5 m/s was associated with almost 90% increase in the risk of events (death or AVR) 27. These studies undeniably validated Vmax as an outcome marker in AS, but the cutoff for identifying patients in whom the severity of the valvular obstacle is critical remains unclear, especially for patients with no or minimal symptoms, as reflected by the different criteria used to define “very severe AS” proposed by US and European guidelines 1, 2.…”
Section: Discussionmentioning
confidence: 97%
“…Although a watchful waiting approach is generally justified in asymptomatic patients with severe AS, there are still concerns about when such a strategy should occur 27. Because improved surgical techniques have led to lower operative mortality and morbidity rates, earlier intervention has been increasingly advocated 3, 4, 5. Another recent report revealed that an initial SAVR strategy in patients with asymptomatic severe AS was associated with a lower risk for all‐cause mortality compared with a conservative watchful waiting approach 6.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent Western guidelines, early invasive therapy is strongly recommended for symptomatic patients with severe AS because of their poor prognosis 1, 2. Based on the current low periprocedural mortality rates for isolated surgical aortic valve replacement (SAVR), earlier surgery for asymptomatic patients with severe AS has been increasingly advocated 3, 4, 5, 6. These studies suggest that early treatment of severe AS may improve the patient's prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although the risk of sudden death in asymptomatic patients with severe AS is low (<1%/year), once symptomatic 3% of patients may die within 6 months, with an overall mortality of 50% over 2 years 3, 4, 5, 6. The decision about timing of AVR in patients with significant AS requires a careful assessment of the risk–benefit ratio of AVR versus watchful waiting.…”
Section: Introductionmentioning
confidence: 99%